The Effect of STEM Integrated Science Innovative Learning Model on Students' Critical Thinking Skills: A Meta-Analysis - Lidya Jasmi; Marjuni Marjuni; Nailul Rahmah Pohan; Asrizal; Fatni Mufit (Jurnal Penelitian Pendidikan IPA, 2023)
This research is a meta analysis. This study aim to analyze the effect of STEM integrated science innovative learning model on students' critical thinking skills. The data collection technique used is the literature review technique, namely by searching and collecting journal articles taken from Google Scholar. Data analysis used quantitative descriptive statistical analysis which aims to obtain effect size values. Based on a meta-analysis of 20 research articles, information was obtained that in general the STEM integrated science innovative learning model has a high influence on students' critical thinking skills with a value of 1.10. If we look at the level of education, education area and learning model, they show that there are significant differences in each field. The greatest impact of STEM is seen at the college level.